ANALISIS MANAJEMEN RISIKO OPERASIONAL PADA USAHA MIKRO KECIL DAN MENENGAH (UMKM) STUDI KASUS LISHA LAUNDRY SUNGGAL - Alfiah Hassanah; Muhammad Haris; Annisa Azmi; Dionisius Halawa; Ayunda Fatmasari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Purpose – This study aims to identify, map, and formulate an action plan for mitigating operational risks faced by Lisha Laundry SMEs located in Dusun IV Sei Mencirim, Sunggal. This arrangement is intended to ensure the operational sustainability of the laundry service business can be maintained efficiently. Method – This research uses a qualitative des,criptive method. Primary data was collected through direct observation of daily activities and in-depth interviews about the laundry business workflow. Risk mapping was conducted using a risk register table and risk matrix (Heat Map) based on probability and impact level parameters. Findings – The identification results found 7 main operational risks at Lisha Laundry. Through matrix analysis, 2 risks were categorized as extreme risk (score 20), namely the risk of clothes being mixed up or lost, as well as the risk of labor shortage during peak days. The main problem stems from human factors (minimal attention to detail) and the way handling methods are mixed on the ironing table. A tactical action plan in the form of implementing a structured Standard Operating Procedure (SOP) has proven crucial in reducing losses.